Editorial [Hot Topic: At Long Last: A Viable Biomedical Model for Fibromyalgia (Daniel J. Wallace (Editor-in-Chief) ] - Wallace, Daniel J. (Current Rheumatology Reviews, 2007)
Fibromyalgia (FM) is a syndrome and not a disease. Six million people in the United States have FM and it costs society 14 billion annually in lost productivity. Since patients don't succumb and are rarely hospitalized for FM, its evolution into an entity with a distinct epidemiology, etiopathogenesis, clinical presentation, laboratory abnormalities and therapy has lagged behind other conditions. Further compounding this is been the debate over provenance: should the primary treating physician for FM be in neurology, physical medicine, orthopedics, rheumatology, internal medicine or psychiatry? For example, the American College of Rheumatology (ACR) endorsed an ad hoc committee's preliminary criteria for FM, only to have the organization's president in his national address posit that the syndrome should not be treated by rheumatologists. Further, some practitioners published opinions that “feeling out of sorts” is a nondisease which does not deserve the cachet of even being a syndrome. The individuals who articulated these concerns wrote editorials but never conducted any evidence based studies validating these opinions. While the fibromyalgia dialog has been in full intercourse since the publication of the ACR criteria in 1990, some investigators have been quietly working to craft a biomedical model which embraces its pathophysiologic abnormalities and translationally apply it to the chronic widespread pain and fatigue our FM patients endure. Roland Staud is an outstanding example of a “bench to bedside” Renaissance man. His prescient work elucidated the mechanisms of the “wind up” phenomenon of pain experienced by FM patients in the Melzack/ Wall “gate theory” context. However, he has also able to convey to a lay audience appreciation of the syndrome with his popular work, “Fibromyalgia for Dummies”. Dr. Staud's contribution to this issue of Current Rheumatology Reports represents the most comprehensive and readable compendium published to date on the biomedical model of FM. In his summary, the chief autonomic, hormonal, muscular, local myofascial, neurotransmitter, cytokine, and stress facets of the syndrome are elegantly woven together in a reader friendly presentation which should help crystallize a practitioner's understanding of what FM constitutes. We are proud to be able to offer these insights to you.